CONSIDERATIONS REGARDING THE LEGISLATIVE FRAMEWORK FOR THE DEVELOPMENT OF THE MOUNTAIN AREA IN ROMANIA - Dănuț UNGUREANU; Aurel CHIRAN; Elena LEONTE; Ion DONA; Cătălin Răzvan VÎNTU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Romania’s mountain area constitutes a defined geographic, economic and social entity, with specific climate, relief, natural and socio-cultural heritage, an identity recognized in Europe and all over the world. The paper aims to analyze the main normative acts for the mountain area in Romania developed after 1990, focusing on the specific legislation of the last 7 years. The aim was to create the legislative framework created, starting with the delimitation of the mountain area - to which this legislation is addressed, the public institutions established for the mountain area, as well as the main provisions to support the mountain population, producers and entrepreneurs in this area. The study of documents was used as research methods: laws, government decisions, ministerial orders, as well as content observation or analysis. The data were collected and interpreted. Results obtained: The 3 official delimitations of the existing mountain area during the studied period were identified and presented, the normative acts by which they were legislated as well as the main criteria that were the basis of each of these delimitations. It should be noted that the delimitation has undergone changes over time, depending on the instruments, policies and legislation existing at each of the times when they were developed. The main public institutions, with a role in the development of mountain areas and the application of public policies, were also identified. The development of mountain areas is achieved through specific policies. The Law of the Mountain and the subsequent laws elaborated, aim to support mountain producers, entrepreneurs and implicitly to lead to the development of mountain areas. By acquiring the right to use the optional quality mention "mountain product", at the level of the mountain area in Romania a Register and a national logo were created and a number of 580 "certified" products were obtained on the end of April 2020. Another 5 laws that provide for investments in this area are being drafted and are waiting to be implemented.